2017
DOI: 10.4172/2169-0286.1000157
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Employee Uniforms on Job Satisfaction in the Hospitality Industry

Abstract: Uniforms play a major role during any service encounter and can impact stakeholder experience. The authors review current literature in the field of uniform provision in the hotel industry and present a comparative study from two different cultural settings: Hong Kong SAR, China and Tyrol, Austria. The research gathered quantitative data from those that wear business attire or uniforms and are engaged in the provision of services and or products alike. The data presents six factors, which describe uniform wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Businesses, both small and large, especially those just starting out, are using this strategy to differentiate themselves from their competitors. Karch and Peter (2017) support this claim by examining how employee uniforms affect customer and employee own satisfaction. The study found that uniforms have a significant impact on employee functionality and customer satisfaction.…”
Section: Tablementioning
confidence: 93%
“…Businesses, both small and large, especially those just starting out, are using this strategy to differentiate themselves from their competitors. Karch and Peter (2017) support this claim by examining how employee uniforms affect customer and employee own satisfaction. The study found that uniforms have a significant impact on employee functionality and customer satisfaction.…”
Section: Tablementioning
confidence: 93%
“…Uniform is one of the factors that has impact on employee performance, way of behavior and job satisfaction (Karch & Peters, 2017). And it is explained that uniforms can affect the working process as well as it increases employee motivation towards common objectives because they feel like they truly are a part of the business (Motivate Your Store Employees With Custom Uniforms, 2019).…”
Section: Uniformmentioning
confidence: 99%